ANALISIS KINERJA KEUANGAN PT. KIMIA FARMA TBK DENGAN PT. INDOFARMA TBK SEBELUM PANDEMI DAN PADA SAAT PANDEMI COVID-19 - Eling Ri Kurniati; Walid Rudianti; Tryan Adhi Nugroho (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2022)
ABSTRACT The Covid-19 pandemic has an impact on the economic sector which has resulted in companies experiencing a decline in financial performance. This study aims to determine whether there are differences in the financial performance of PT. Kimia Farma Tbk. and PT. Indofarma Tbk. before the pandemic and during the covid-19 pandemic. This type of research is quantitative research with secondary data analysis and uses a comparative approach method. Sampling with purposive sampling method. Data collection techniques used are documentation techniques on financial reports published by PT. Kimia Farma Tbk. and PT. Indofarma Tbk. obtained from the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id. Then processed using the SPSS Version 16.0 application and the test used in this study is a comparative test, namely the Wilcoxon Sign Test. The results of this study indicate that there are significant differences in PT. Kimia Farma Tbk. based on liquidity ratios, solvency ratios, activity ratios and profitability ratios. As for PT. Indofarma Tbk. also the same, there are significant differences based on liquidity ratios, solvency ratios, activity ratios and profitability ratios. PT. Kimia Farma Tbk. has a better performance than PT. Indofarma Tbk. before the pandemic or during the pandemic.